An unusual presentation of pulmonary lymphoma: When diffuse ground glass opacities can mean anything - Stainer, Anna; Faverio, Paola; Bono, Francesca; Pesci, Alberto (Monaldi archives for chest disease, 2018)
Primary lung lymphoma (PLL) is a rare type of lymphoma confined to the lung at the time of diagnosis. Pulmonary diffuse large B cells lymphoma (P-DLBCL) is the second most common type of PLL and it usually appears radiologically as solitary or multiple nodules or areas of consolidation. We present the case of a 63-year-old Caucasian male who developed severe acute respiratory failure and diffuse ground glass opacities (GGO) on chest computerized tomography. Diffuse GGO may be the radiological expression of very different diseases, ranging from infectious processes to interstitial lung diseases (ILDs) and neoplastic diseases. In our case, pneumonia and de novo ILD were initially considered given the symptoms and past medical history. However, bronchoscopy with trans-bronchial biopsies demonstrated the presence of P-DLBCL, despite an unusual radiological presentation and negative cytological analyses on bronchoalveolar lavage. In conclusion, P-DLBCL should be considered among the many differential diagnoses of diffuse GGO.